Assessing productivity and profitability of a rejuvenated ber (Ziziphus mauritiana) based agri-horti system under arid rainfed conditions - SINGH, AKATH; TANWAR, S P S; MEGHWAL, P R; SAXENA, ANURAG; KUMAR, MAHESH (The Indian Journal of Agricultural Sciences, 2018)
A field experiment was carried out at ICAR-Central Arid Zone Research Institute, Jodhpur, Rajasthan from 2011-15 to make senile orchard (33 years old) remunerative again. Trees were headed back from ground level in summer. Out of the numerous shoots emerged, 1-2 shoots were budded with early, mid and late season’s cultivar. In subsequent years, inter-cropping was carried out in the ber (Ziziphus maurtitiajna Lam.) alleys with greengram (Vigna radiata L.), pearlmillet (Pennisetum glaucum L.) and senna (Cassia angustifolia) at two alleys spacing, i.e. 6 m and 12 m (plant to plant spacing in both the alleys was 6 m) tested over three ber varieties, viz. Gola, Seb and Umran in split-plot design replicated thrice. The rejuvenated trees attained profitable yield level within three years of rejuvenation. Gola ber recorded highest productivity (57.3 q/ha) followed by Seb and Umran. Amongst intercrops, the productivity of greengram as ber equivalent yield was 1.7 and 4.2 times higher over pearl millet and senna, respectively. Although, wider spacing increased the productivity of intercrops by 24%. But, the total system productivity in wider ber alleys was 50.47% less during first year followed by 30.3, 34.6 and 40% during subsequent years, respectively, compared to 6 m × 6 m spacing. The profitability was also higher under 6 m × 6 m spacing. The ber + greengram system gavehighest net returns (84.79 ×103 Rupees/ha) over other. This agri-horti system also maintained the initial soil fertility status even after four crop cycles. Hence, the appropriate strategy should be to introduce intercrops preferably green gram at a recommended spacing (6 m × 6 m) of ber variety Gola for highest system productivity and profitability.